Influence of Arbuscular mycorrhiza on the growth potential of Entandrophragma cylindricum seedlings (Agriculture, Food, and Natural Resources Journal, 2024)
The study assessed the effects of Arbuscular mycorrhiza on the growth of Entandrophragma cylindricum seedlings, valued for their premium timber and medicinal properties. Seeds were germinated, and 42 healthy seedlings were transplanted into pots containing 2 kg of topsoil, treated with varying amounts of A. mycorrhiza (30 g, 60 g, 90 g, 120 g, and 150 g), alongside a control group without mycorrhiza. The study utilized a Completely Randomized Design (CRD) and measured variables such as plant height, stem diameter, leaf area, biomass accumulation, chlorophyll content, and leaf count. The results showed that the 120 g treatment produced the best growth: an average height of 37.48 cm, a stem diameter of 6.33 mm, and 17.14 leaves, along with higher biomass and chlorophyll levels. In contrast, the control group exhibited the lowest growth, with only 8 leaves and a height of 13.55 cm. Statistical analysis revealed significant differences in height, stem diameter, leaf area, and leaf count, while biomass and total chlorophyll showed no significant differences. The interaction between A. mycorrhiza and soil nutrients was significant, indicating a positive effect on seedling growth. It is recommended to use 120 g of A. mycorrhiza for nursery cultivation to achieve robust growth and high yields of E. cylindricum.
Keywords: Arbuscular Mycorrhiza; Entandrophragma cylindricum; Growth-Potential; Seedlings